Start-ups and employment growth: evidence from Sweden - Martin Andersson; Florian Noseleit (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We use longitudinal data over a decade on start-ups and employment in Swedish regions and analyze the effect of start-ups on subsequent employment growth. We extend previous analyses by examining the influence of regional start-ups in a sector on regional employment growth in the same sector and on other sectors. We find differences between different types of start-ups. Knowledge-intensive start-ups seem to have larger effects on the regional economy. In particular, start-ups in high-end services have significant negative impacts on employment in other sectors but a positive long-run impact. This is consistent with the idea that start-ups are a vehicle for changes in the composition of regional industry. Moreover, our results illustrate that the known S-shaped pattern can be attributed to different effects that start-ups in a sector have on employment change in the same sector and in others.
Keywords: J23; M13; O52; 330; Entrepreneurship; employment growth; regional development; start-ups; Unternehmensgründung; Unternehmer; Regionale Entwicklung; Regionaler Strukturwandel; Regionaler Arbeitsmarkt; Schweden